COMMUNICATIVE TOLERANCE OF HIGHER EDUCATION STUDENTS AS A SOCIAL FACTOR IN THE SHAPING OF THE LEARNING ENVIRONMENT - Kontsevich, Galina; Burakova, Irina; Sitak, Larisa (Revista Inclusiones, 2020)
Tolerance is one of the most significant socio-psychological attitudes and behavioral traits of people and social groups. The causes of tolerance and, all the more so, of destructive tolerance in the present-day socio-cultural, economic and political context, have steadily grown in number, hence the need for a multidimensional study and explanation of these phenomena. The authors examined the communicative tolerance of higher education students in the Caucasian Mineral Springs area by taking a socio-economic measurement of the level of development of qualities and characteristics of intolerant people in terms of interpersonal relationships. The research study was carried out in the following higher educational institutions: the Institute of Services, Tourism and Design (campus) of the Pyatigorsk State University, the North-Caucasus Federal University and the Zheleznovodsk Campus of the Stavropol State Pedagogical Institution. The survey conducted in March and April 2019 among 240 respondents, aged 18 to 25, revealed that intolerance is one of the distinctive psychological traits peculiar to this age group.